Characterization of An Acrylamide-degrading Bacterium Isolated from Volcanic Soil - Rusnam, .; Gusmanizar, Neni (Journal of Environmental Bioremediation and Toxicology, 2022)
Due to the fact that it breaks down into acrylamide over time, polyacrylamide is one of the most important sources of acrylamide in soil. As a strategy for bioremediation, the breakdown of acrylamide by the action of microbes has seen a gradual but consistent increase in attention all over the world. In this work, a bacterium, tentatively identified as Pseudomonas sp. strain Neni-12 that had been isolated from volcanic soil showed the ability to grow on acrylamide. The acrylamide-degrading bacterium grew best in the presence of glucose with acrylamide as the sole nitrogen source. At concentrations of acrylamide ranging from 400 to 600 mg/L, the organisms saw the greatest amount of growth, where ANOVA analysis shows no difference among these temperatures; however, growth was entirely halted at concentrations of 800 mg/L and above. The optimum pH was at 7.0, and growth was maximum between 25 and 35 °C. The bacterium is also capable of growing while using acetamide as the only source of nitrogen. An acrylamide-degrading bacterium that was isolated from volcanic soil is reported for the very first time here.